The Role of Self-Efficacy in Bridging the Influence of Financial Literacy and Competency Development on Students' Work Readiness - Fajar Budiyanto; Trijadi Herdajanto (JURNAL ECONOMINA, 2026)
This study aims to examine the effect of financial literacy and self-competency development on students’ work readiness through self-efficacy as a mediating variable. The research employed a quantitative approach with an explanatory research design. The population consisted of students from the Faculty of Economics at Universitas Mayjen Sungkono, with a sample of 157 respondents selected using probability sampling through a simple random sampling method. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The findings reveal that financial literacy and self-competency development have a positive and significant effect on students’ work readiness. Furthermore, financial literacy and self-competency development were found to positively influence self-efficacy. Self-efficacy also has a positive effect on work readiness and serves as a mediator in the relationship between financial literacy, self-competency development, and students’ work readiness. These findings indicate that students’ work readiness is not only determined by knowledge and competency factors but also by individuals’ confidence in their ability to face workplace demands. This study supports Social Cognitive Theory by demonstrating that cognitive factors, learning experiences, and personal factors interact in shaping students’ work readiness.